José María Salvador-González, Thalamus Dei. The Bed in Images of the Annunciation Its Iconography and Doctrinal Explanation, Editorial Sindéresis / Editorial Dykinson, Madrid 2024, s. 188. - Roszak, Piotr (Studia Gdańskie, 2024)
José María Salvador-González, Thalamus Dei. The Bed in Images of the Annunciation Its Iconography and Doctrinal Explanation, Editorial Sindéresis / Editorial Dykinson, Madrid 2024, s. 188.